Identification of Effective Strategies for Blended Learning in Physical Education at Islamic Azad University - Ghavidel Bajgiran, Meisam; Hamboushi, Laleh (Health Nexus, 2024)
This study aims to identify effective strategies for utilizing blended learning in the Physical Education course at Islamic Azad University. The present research was conducted qualitatively using thematic analysis. To this end, semi-structured interviews were conducted with 14 faculty members from the Islamic Azad University of Razavi Khorasan Province, who were selected purposefully and judgmentally. The thematic network method was employed in this research. The validity and reliability of the study were examined and confirmed using the method of Guba and Lincoln (1985). After completing the interview and coding process, 47 basic themes, 11 organizing themes, and 3 global themes (individual capabilities, educational processes, and organizational policy) were identified. Based on the findings, it can be concluded that educational planners and designers at the university can use the results obtained to develop, design, implement, and evaluate based on the needs of the university and its audience. The findings of this research can help Islamic Azad University achieve its macro goals and policies based on the university’s statute and facilitate blended learning in the Physical Education course.